Impact of a Vancomycin-Induced Shift of the Gut Microbiome in a Gram-Negative Direction on Plasma Factor VIII:C Levels: Results from a Randomized Controlled Trial - Grimnes, Gro; Bhoelan, Soerajja; Hindberg, Kristian; Davids, Mark; Nieuwdorp, Max; Mollnes, Tom E.; Michelsen, Annika E.; Ueland, Thor; Brækkan, Sigrid K.; Hansen, John-Bjarne; Tichelaar, Vladimir (Thrombosis and Haemostasis, 2021)
Background Inflammation is present in several conditions associated with risk of venous thromboembolism. The gut microbiome might be a source of systemic inflammation and activation of coagulation, by translocation of lipopolysaccharides from gram-negative bacteria to the systemic circulation.Objective To investigate whether a vancomycin-induced shift of the gut microbiome in a gram-negative direction influences systemic inflammation and plasma factor (F) VIII procoagulant activity (FVIII:C).Methods and Results We performed a randomized controlled trial including 43 healthy volunteers aged 19 to 37 years. Twenty-one were randomized to 7 days of oral vancomycin intake and 22 served as controls. Feces and blood were sampled at baseline, the day after the end of intervention, and 3 weeks after intervention. Gut microbiome composition was assessed by amplicon sequencing. FVIII:C was measured using an activated partial thromboplastin time-based assay, cytokines were measured using multiplex technology, complement activation was measured using the enzyme-linked immunosorbent assay, and high-sensitivity C-reactive protein (CRP) was measured by an immunoturbidimetric assay. Vancomycin intake reduced gut microbiome diversity and increased the abundance of gram-negative bacteria. Change in FVIII:C in the intervention group was +4 IU/dL versus −6 IU/dL (p = 0.01) in the control group. A similar change was observed for log-transformed CRP (+0.21 mg/dL vs. −0.25 mg/dL, p = 0.04). The cytokines and complement activation markers remained similar in the two groups.Conclusion The found slight increases in FVIII:C and CRP levels might support the hypothesis that a vancomycin-induced gram-negative shift in the gut microbiome could induce increased systemic inflammation and thereby a procoagulant state.
Keywords: microbiome; inflammation; coagulation; randomized controlled trial